Annual plant reviews, Volume 34: Molecular aspects of plant disease resistance - Parker, Jane (Wiley-Blackwell, 2012)
In recent years, our understanding of the mechanisms involved in a plant's resistance to attack by disease, has seen major advances. This important new title, part of Blackwell Publishing's Annual Plant Reviews Series, provides cutting edge reviews of each of the major aspects of the subject.